Reconstrução vesical em cães após cistectomia supratrigonal utilizando cólon descendente ou bexiga homóloga conservada em glicerina - Bajotto, Gustavo Cancian (2001)
Ten dogs were submitted to the supratrigonal cystectomy, with the objective of testing the viability of using the tubularized descending colon, to vesical reconstruction. A segment of the colon was sectioned and transformed into a pouch through a suture of its cranial edge. The graft was sutured to the bladder in two layers with 5-0 poliglactin. The caudal mesenteric artery kept the vascular pedicle. The necropsies carried through at the days 30 and 60 showed adherences in all dogs, perforation in one, necrosis of the graft in three and peritonitis were founding in two. The upper urinary tract remained without macroscopic alterations. In the histological analysis, necrosis of the graft was observed in three cases without happen reepitelization even after the loss of the mucosa. Despite the observed complications and the small volume, the new bladder remained functional and the upper urinary tract was preserved. The tubularized descending colon can be used for the bladder replacement after partial cystectomy.